Yusuf Al-Qardhawi's Thoughts and Their Implementation to Indonesian Society - Ujang Supriyadi (Jurnal Syntax Transformation, 2023)
Islam is actually a religion that provides security, comfort, tranquility and tranquility for all its creatures. There is nothing in Islam that teaches its people to hate and harm others. Islam as a perfect religion, namely a religion that brings mercy to the universe (rahmatan lil alamin) always prioritizes the mission of peace, tolerance, moderation and nonviolence. This adaptive and accommodating characteristic of Islam is what the Prophet Muhammad (PBUH) championed. A religion that is easily accepted because its teachings are humane and universal. Historically, the entry of Islam in Indonesia was very peaceful and tolerant, as taught by the saints through local culture and could coexist with other religions at that time. But at this time violence or extreme attitudes are a phenomenon that we often hear and see, both in the mass media and the reality that surrounds our environment and society. The phenomenon of Islamic religious discourse in post-reform Indonesia is suspected to have experienced a lot of radicalism and even extremism. The explosion of terrorism in the name of Islam that occurred after the reform until now has made the face of Indonesian Islam in the spotlight in the world. In fact, Islam in Indonesia is Islam that prioritizes moderate principles (al-washathiyyah) in preaching, this characteristic of accommodating Islam is the bulwark of preventing radical religious understanding. Therefore, this study examines more focus and detail about how the concept of Al-Wasatiyyah in Islam according to Yusuf Al-Qaradawi and its implications for Indonesian society.